Impact of an empiric antimicrobial therapy manual on antimicrobial usage and multidrug resistant organism trends in a large Italian teaching hospital - Silvia Corcione; Nour Shbaklo; Costanza Vicentini; Alessio Corradi; Silvia Scabini; Simone Mornese Pinna; Alessia Tarozzo; Antonio Curtoni; Francesco Cattel; Rossana Cavallo; Carla M. Zotti; Ida Marina Raciti; et al. (Elsevier, 2022)
Summary: Aim: To evaluate the changes in antimicrobial consumption and multidrug-resistant microorganism trends after introducing an empiric antimicrobial therapy manual to support antimicrobial stewardship. Methods: A 4-year prospective interventional study assessed the effect of introducing an empiric antimicrobial therapy manual in medical and surgical wards during two periods: pre-intervention period (January 2015-May 2017) and post-intervention period (June 2017-December 2019). Outcomes included microorganism trends of bloodstream infections (BSI) for Klebsiella pneumoniae carbapenemase-producing bacteria (KPC), extended spectrum beta-lactamase ESBL-E. coli, meticillin-resistant Staphylococcus aureus (MRSA) and Candida albicans. Also, Clostridioides difficile infection (CDI) episodes were included. Rates were normalised per 1000 patient-days (PD). Antimicrobial consumption was assessed as defined daily dose (DDD)/1000 PD in interrupted time series analysis. Results: In medical wards, we observed a significant decrease in the consumption of piperacillin-tazobactam and a decrease in the trends of tigecycline and vancomycin consumption. In surgical wards, there was a significant decrease in consumption of fluoroquinolones and piperacillin-tazobactam. This decrease was maintained in trend for all the antimicrobials but was significant for tigecycline only. In medical wards, there was a significant reduction of MRSA and C. albicans. In surgical wards, we observed a decrease in MRSA, ESBL-E. coli, C. albicans and CDI. KPC cases decreased by 22.5% in medical wards and 74.3% in surgical wards. Conclusion: The results suggest that a persuasive educational approach to antimicrobial stewardship, with the introduction of an empiric antimicrobial manual and continuous education, resulted in reductions in both antimicrobial use and healthcare-associated BSI caused by multidrug-resistant organisms. More studies with longer follow up are needed to investigate the effect of antimicrobial stewardship on clinical outcomes.